Art Integration in Teaching: An Approach in Intensifying Performance in Trigonometry - Caibigan, Agnes M. (8ISC Abstract Proceedings, 2022)
Teaching Mathematics in the New Normal requires a lot of effort to get students’ interest to make them learn independently due to limited time of teacher-student interaction. With the current pandemic, this has become more challenging for Math teachers in the online distance learning set-up, especially with students’ short attention span. According to Ochshorn (2016), topics integrated with art have shown higher efficacy. In this regard, this study was conducted to determine the effectiveness of art integration in teaching Trigonometry to selected Grade 9 online distance learning students of Paliparan National High School. Sixty students from the four sections in Grade 9 were randomly selected to participate. A standardized 30-item test was used as the statistical instrument. The researcher applied a pre-test-post-test design. The control group used the existing method, which is the Learning Management System, while the experimental group used Art modules on their asynchronous learning tasks. T-test was used as the statistical treatment for the study. When the pre-test and post-test performance of students taught Mathematics with the use of Art Integration were compared, results assert an improvement. Moreover, when the Mean Gain of students taught in Mathematics without and with the use of art integration was compared, it indicates that the approach used in both groups is equally effective. Thus, Art Integration intensifies student performance in Trigonometry. Research findings concluded with some pedagogical implications for teachers and instructional material writers such as book authors, module creators, and web developers. Further studies are recommended to investigate if the result will be the same in the Modular Distance Learning modality and when conducted to a wider scope of respondents. Keywords : Art Modules, Art Integration, Learning Management System, Mathematics, Online Distance Learning, Online Learning Modality, Trigonometry